Self-assembled monomolecular film hole transport material based on diphosphoric acid and preparation method and application thereof

By using self-assembled single-molecular film hole transport materials based on bisphosphate in perovskite solar cells, the problems of high cost and poor compatibility of traditional materials are solved, the performance and stability of the device are significantly improved, and efficient photoelectric conversion efficiency is achieved.

CN119591639AActive Publication Date: 2025-03-11SUZHOU LIWEI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411594303.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-03-11
Estimated Expiration
2044-11-09

AI Technical Summary

Technical Problem

In existing perovskite solar cells, traditional hole transport layer materials have problems such as high cost and poor compatibility with perovskite interfaces, which limits the long-term stability of the device and the large-scale commercialization process.

Method used

Self-assembled single-molecular membrane hole transport material based on bisphosphate is used, and the self-assembly of methoxycarbazole is used as the main core, alkyl chain or benzene ring is used as the connecting unit, and bisphosphate is used as the anchor group to enhance the chelation with the conductive base and improve the self-assembly characteristics and interface stability of the material.

Benefits of technology

The performance and stability of perovskite solar cells were significantly improved, with the short-circuit photocurrent density reaching 25.64mAcm-2, the open circuit voltage is 1.145V, the filling factor (FF) is 0.8407, and the photoelectric conversion efficiency reaches 24.7%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591639A_ABST
    Figure CN119591639A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite solar cells, and particularly discloses a self-assembly monomolecular film hole transport material based on diphosphoric acid and a preparation method and application thereof.The diphosphoric acid serves as an anchoring group, the chelation between the material and a conductive base can be effectively enhanced, the self-assembly characteristic of the material on the surface of a substrate is improved, and the hole transport efficiency is improved. The compact and smooth self-assembled monomolecular film is formed. Meanwhile, the electron and space effects of alkyl chains or benzene ring connecting units are regulated and controlled, so that the molecular stereo configuration and energy level matching are optimized. The material disclosed by the invention is simple in synthesis steps and low in preparation cost, and industrial synthesis of the material can be realized. When the material is applied to an inverted perovskite solar cell as a hole transport layer, photoelectric conversion efficiency exceeding 24.7% and excellent device stability performance can be obtained, and huge commercial prospects are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cells, and relates to the research and development of inverted structure perovskite solar cell interface materials, and specifically relates to a self-assembled monomolecular film hole transport material based on bisphosphoric acid, and a preparation method and application thereof. Background Art

[0002] As the global demand for renewable energy continues to grow, solar cells have received widespread attention as a green energy conversion device. Perovskite solar cells have become one of the most promising new generation photovoltaic technologies after silicon-based solar cells due to their excellent photoelectric conversion efficiency, simple preparation process and low cost. In recent years, organic-inorganic hybrid perovskite solar cells (PSCs) have made rapid progress with their unique photoelectric properties, and the photoelectric conversion efficiency (PCE) has jumped from 3.8% to 26.7%. The application of self-assembled hole transport materials in perovskite solar cells marks an important advancement in the field of photovoltaic technology.

[0003] However, while pursuing high performance, how to ensure the long-term stable operation of PSCs has become one of the major challenges faced by researchers. Among them, the hole transport layer is a key component that affects device performance. Although traditional HTL materials such as poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA) are widely used, they have problems such as high cost and poor compatibility with the perovskite interface, which limits the large-scale commercialization of PSCs.

[0004] In this context, self-assembled monolayers have gradually come into people's view as a new type of HTL material. SAM has unique structural characteristics: it can be directly fixed on the surface of the substrate through chemical bonds to form a uniform and dense film; at the same time, by carefully designing the molecular structure, the energy level matching between SAM and perovskite can be adjusted to optimize the charge separation efficiency. In addition, compared with traditional organic HTL materials, the amount of material required for SAM is extremely low, which not only helps to reduce production costs, but also reduces the impact on the environment. More importantly, properly selected or modified SAM can significantly improve the working stability of PSCs, which is crucial to promoting this technology from the laboratory to practical applications.

[0005] Therefore, exploring efficient, stable and economical self-assembled hole transport materials suitable for perovskite solar cells has become one of the current scientific research hotspots, and is expected to provide new ideas and technical support for solving the problems encountered in the industrialization process of PSCs. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a self-assembled monomolecular film hole transport material based on bisphosphonic acid. The present invention uses methoxycarbazole as the main core, alkyl chains or benzene rings as connecting units, and bisphosphonic acid as an anchoring group, which can effectively enhance the chelation effect with the conductive base, improve the self-assembly properties of the material on the substrate surface, thereby improving the perovskite film quality, inhibiting non-radiative recombination between interfaces, and improving the performance and stability of the device.

[0007] The present invention is achieved through the following technical solutions:

[0008] A self-assembled monolayer hole transport material based on bisphosphoric acid, the chemical structure of which is selected from the following structures:

[0009]

[0010] A further improvement of the present invention is:

[0011] A method for preparing a self-assembled monomolecular film hole transport material based on bisphosphoric acid comprises the following steps:

[0012] (1) coupling reaction of the compound of formula 1 with 1,4-dibromobutane to generate intermediate 2;

[0013] (2) allowing intermediate 2 to undergo a substitution reaction with tetraethyl methylene diphosphonate to generate intermediate 3;

[0014] (3) hydrolyzing the intermediate 3 with bromotrimethylsilane to generate the target product 4;

[0015] The reaction route is as follows:

[0016]

[0017] Furthermore, the specific process of step one is: mixing compound 1, 1.4-dibromobutane, tetrabutylammonium bromide and potassium hydroxide aqueous solution, reacting at 60-80°C for 5-8 hours to obtain intermediate compound 2; wherein the molar ratio of compound 1, 1.4-dibromobutane, tetrabutylammonium bromide and potassium hydroxide is 1:8-10:0.01-0.03:10-12.

[0018] Furthermore, the reaction in step 2 is carried out under nitrogen gas protection, with sodium hydride as a strong base and tetrahydrofuran as a solvent, so that the intermediate compound 2 reacts with diethyl phosphite at a temperature of 0-70°C to obtain the intermediate compound 3; wherein the molar ratio of the intermediate compound 2, sodium hydride and tetraethyl methylene diphosphate is 1:1.5~2.0:1~2.

[0019] Furthermore, the reaction in step three is carried out under nitrogen gas protection, using 1.4-dioxane as solvent and trimethylsilyl bromide as hydrolysis reagent, so that the intermediate compound 3 undergoes hydrolysis reaction at a temperature of 0-50°C to obtain the final product 4, and methanol is used as a quenching reagent after the reaction; wherein the molar ratio of the intermediate compound 3 to trimethylsilyl bromide is 1:5-10.

[0020] A further improvement of the present invention is:

[0021] A method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid, characterized in that it comprises the following steps:

[0022] (1) coupling reaction of the compound of formula 1 with 1,3-dibromo-5-iodobenzene to generate intermediate 5;

[0023] (2) causing intermediate 5 to undergo a substitution reaction with diethyl phosphite to generate intermediate 6;

[0024] (3) hydrolyzing the intermediate 6 with bromotrimethylsilane to generate the target product 7;

[0025] The reaction route is as follows:

[0026]

[0027] Furthermore, the specific process of step one is: dissolving compound 1, 1.3-dibromo-5-iodobenzene, cuprous iodide, 18-crown-6 and potassium carbonate in N,N-dimethylpropylene urea, and reflux reacting under a nitrogen atmosphere to obtain an intermediate compound 5; wherein the molar ratio of compound 1, 1.3-dibromo-5-iodobenzene, cuprous iodide, 18-crown-6 and potassium carbonate is 1:1~3:0.1~0.2:0.05~0.1:2~6.

[0028] Furthermore, the specific process of step 2 is: dissolving intermediate 5, diethyl phosphite, palladium acetate, potassium acetate and dppf in 1.4-dioxane, heating and refluxing to obtain intermediate compound 6, wherein the molar ratio of compound 5, diethyl phosphite, palladium acetate, potassium acetate and dppf is 1:30-40:0.05-0.15:4-8:0.1-0.5.

[0029] Furthermore, step three is carried out under nitrogen gas protection, using 1.4-dioxane as solvent and trimethylsilyl bromide as hydrolysis reagent, so that the intermediate compound 6 undergoes hydrolysis reaction at a temperature of 0-50°C to obtain the final product 7, and methanol is used as a quenching reagent after the reaction; wherein the molar ratio of the intermediate compound 6 to trimethylsilyl bromide is 1:10-30.

[0030] A further improvement of the present invention is:

[0031] The above-mentioned self-assembled single-molecule hole transport material based on bisphosphonic acid is used in inverted structure perovskite solar cells.

[0032] The beneficial effects of the present invention are:

[0033] 1. A self-assembled monolayer hole transport material based on a bisphosphonic acid anchoring group of the present invention, with methoxycarbazole as a substrate and bisphosphonic acid as an anchoring group, the introduction of bisphosphonic acid can effectively enhance the chelation between the material and the conductive base, and help to achieve complete coverage and firm bonding of the self-assembled monolayer hole transport material on the substrate surface, thereby improving the interface stability and reducing non-radiative recombination at the interface;

[0034] 2. Using methoxycarbazole as the parent core, the molecular dipole and interface properties are regulated to improve the photovoltaic performance of the material. At the same time, the molecular stereo configuration and energy level matching are optimized by regulating the electronic and spatial effects of the alkyl chain or benzene ring connecting unit.

[0035] 3. When the self-assembled monolayer provided by the present invention is applied to an inverted perovskite solar cell, the short-circuit photocurrent density of the short-circuit photocell device reaches 25.64 mA cm -2 , the open circuit voltage is 1.145V, the fill factor (FF) is 0.8407, and the photoelectric conversion efficiency reaches 24.7%, which has practical significance for improving the efficiency of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The hole transport material 4 prepared in Example 1 1 H NMR spectrum;

[0037] Figure 2 The hole transport material 7 prepared in Example 2 1 H NMR spectrum;

[0038] Figure 3 4 is the JV curve of the inverse perovskite solar cell prepared as a self-assembled monolayer;

[0039] Figure 4 7 is the JV curve of the inverse perovskite solar cell prepared as a self-assembled monolayer; DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with specific embodiments.

[0041] Example 1: Synthesis of Alkyl Chain Diphosphoric Acid Hole Transport Material 4

[0042]

[0043] Step 1:

[0044] Add compound 1 (5.0g 22.02mmol), tetrabutylammonium bromide (0.142g 0.44mmol), 1.4-dibromobutane (24ml 197.86mmol), 50% potassium hydroxide aqueous solution (13.55g 241.96mmol) to a 100ml two-necked bottle, connect the reflux device, and heat to reflux. After monitoring the reaction is complete by thin layer chromatography, turn off the heating, wait for the reaction to cool to room temperature, and add an appropriate amount of water to quench the reaction. Extract with ethyl acetate, dry with anhydrous sodium sulfate or anhydrous magnesium sulfate, then remove 1.4-dibromobutane by reduced pressure distillation, and finally purify the concentrated mixture by silica gel column chromatography (eluent: PE / DCM=5:1, v / v). The purified product is 6.4g of white solid with a yield of 80.3%.

[0045] Step 2:

[0046] Under nitrogen protection, 20 mL of tetrahydrofuran, tetraethyl methylene diphosphate (2.17 g 7.52 mmol) and sodium hydride (0.33 g 13.75 mmol) were added to a 100 mL two-necked flask in sequence, and then compound 1 (3 g 8.3 mmol) dissolved in tetrahydrofuran was slowly added dropwise, and the reaction solution was heated to reflux for 24 h. After the reaction solution was cooled to room temperature, an appropriate amount of water was added to quench the reaction. Extraction with ethyl acetate was repeated three times and dried over anhydrous magnesium sulfate and filtered. The solvent was removed by rotary evaporator to obtain a crude product. The crude product was separated by chromatography column (eluent: PE / EA=10:1, v / v) to obtain 3.3 g of light yellow oil with a yield of 70%. 1 HNMR(400MHz,DMSO-d6)δ7.51(d,J=2.4Hz,2H),7.33–7.17(m,2H),7.08(dd,J=8.8,2.5Hz,2H),4.10(qd,J=6.9,1.4Hz,1 0H),3.92(s,6H),3.86(s,1H),2.26–2.10(m,2H),1.90–1.78(m,2H),1.60(dd,J=9.5,5.0Hz,2H),1.26(t,J=7.0Hz,12H).

[0047] Step 3:

[0048] Under nitrogen protection, compound 3 (3.9 g 1.54 mmol) was added to a 100 mL two-necked flask and connected to a reflux device. After replacing nitrogen three times with a double-row tube, 1.4-dioxane was used to dissolve it. Under an ice bath, trimethylsilyl bromide (20 ml 40.36 mmol) was slowly added dropwise and stirred at room temperature for 24 h. After adding 20 mL of anhydrous methanol to quench the reaction, it was stirred for 3 h, and finally 300 mL of deionized water was added and stirred for 24 h. The reaction solution was filtered and washed with water to obtain 2.0 g of a white solid with a yield of 64%. 1 H NMR (400MHz, DMSO) δ7.71(d,J=2.5Hz,2H),7.43(d,J=8.9Hz,2H),7.04(dd,J=8.9,2.5Hz,2H),4. 26(t,J=7.2Hz,2H),3.85(s,6H),1.86–1.75(m,2H),1.68(d,J=7.4Hz,3H),1.57(d,J=7.2Hz,2H).

[0049] Example 2: Synthesis of phenyl ring diphosphoric acid hole transport material 7

[0050]

[0051] Step 1:

[0052] Under nitrogen protection, compound 1 (2g 8.81mmol), 1.3-dibromo-5-iodobenzene (6.43g 17.8mmol), cuprous iodide (0.25g 1.31mmol), 18-crown-6 (0.180.68mmol) and potassium carbonate (4.87g 35.23mmol) were added to a 100mL two-necked flask in sequence, and the reflux device was connected. After the nitrogen was replaced three times with a double-row tube, the reaction solution was dissolved with DMPU and heated to reflux for 12h. After the reaction solution was cooled to room temperature, an appropriate amount of water was added to quench the reaction. Extracted with ethyl acetate, dried with anhydrous magnesium sulfate and filtered after three times, the solvent was removed by rotary evaporator to obtain a crude product. The crude product was separated by chromatography column (eluent: PE / DCM=10:1, v / v) to obtain 3g of light yellow solid with a yield of 75%. 1 H NMR (400 MHz, CDCl 3 )δ7.93–7.80(m,1H),7.76–7.64(m,4H),7.33(dt,J=8.9,5.7Hz,2H),7.14–6.98(m,2H),3.95(s,6H).

[0053] Step 2:

[0054] Under nitrogen protection, compound 5 (2g 4.35mmol), palladium acetate (0.01g4.08mmol), potassium acetate (2.56g 26.08mmol), dppf (0.46g 0.86mmol) were added to a 100mL two-necked flask in sequence, and the reflux device was connected. After replacing the nitrogen three times with a double-row tube, 1.4-dioxane was used to dissolve it, and then diethyl phosphite was added dropwise. The reaction solution was heated to reflux for 12h. After the reaction solution was cooled to room temperature, an appropriate amount of water was added to quench the reaction. Extracted with ethyl acetate, dried with anhydrous magnesium sulfate and filtered after repeated three times, the solvent was removed by rotary evaporator to obtain a crude product. The crude product was separated by chromatography column (eluent: PE / DCM=10:1, v / v) to obtain 1.87g of light yellow solid with a yield of 75%. 1 HNMR (400MHz, CDCl 3 )δ8.30–8.12(m,3H),7.54(s,2H),7.39–7.27(m,2H),7.05(d,J=8.9Hz,2H),4.40–4.08(m,8H),3.95(t,J=1.5Hz,6H),1.54–1.18(m,12H).

[0055] Step 3:

[0056] Under nitrogen protection, compound 51 (1.95 g 3.35 mmol) was added to a 100 mL two-necked flask in sequence and connected to a reflux device. After replacing nitrogen three times with a double-row tube, 1.4-dioxane was used to dissolve the mixture. Under an ice bath, trimethylsilyl bromide (9 ml 69.4 mmol) was slowly added dropwise and stirred at room temperature for 24 h. After adding 20 mL of anhydrous methanol to quench the reaction, the mixture was stirred for 3 h, and finally 300 mL of deionized water was added and stirred for 24 h. The reaction solution was filtered and washed with water to obtain 1.4 g of a yellow solid with a yield of 89.7%. 1 HNMR (400MHz, DMSO) δ8.12–8.00(m,1H),7.99–7.80(m,4H),7.31(d,J=8.9Hz,2H),7.08(dd,J=8.9,2.6Hz,2H),3.89(s,6H).

[0057] Embodiment 3:

[0058] The self-assembled monolayer compound 4 prepared in Example 1 was used to prepare a perovskite solar cell according to the literature G. Qu; S. Cai; Y. Qiao; et al. Joule, 2024, 8, 2123-2134. The test light source was AM 1.5 (solar simulator-Oriel91160-1000, 300W), and the data was collected using a Keithley 2400 digital source meter. The test results are shown in Figure 3 The short-circuit photocurrent density of the battery device reached 25.60mAcm-2, the open-circuit voltage was 1.144V, the fill factor (FF) was 0.8292, and the photoelectric conversion efficiency reached 24.3%.

[0059] Embodiment 4:

[0060] The self-assembled monolayer compound 7 prepared in Example 2 was used to prepare a perovskite solar cell according to the literature G. Qu; S. Cai; Y. Qiao; et al. Joule, 2024, 8, 2123-2134. The test light source was AM 1.5 (solar simulator-Oriel91160-1000, 300W), and the data was collected using a Keithley 2400 digital source meter. The test results are shown in Figure 3 The short-circuit photocurrent density of the battery device reached 25.64mAcm-2, the open-circuit voltage was 1.145V, the fill factor (FF) was 0.8407, and the photoelectric conversion efficiency reached 24.7%.

[0061] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-assembled monolayer hole transport material based on bisphosphoric acid, characterized in that: The chemical structure is selected from the following structures:

2. The method for preparing a self-assembled monolayer hole transport material based on bisphosphoric acid according to claim 1, characterized in that: The following steps are involved: (1) coupling reaction of the compound of formula 1 with 1,4-dibromobutane to generate intermediate 2; (2) allowing intermediate 2 to undergo a substitution reaction with tetraethyl methylene diphosphonate to generate intermediate 3; (3) hydrolyzing the intermediate 3 with bromotrimethylsilane to generate the target product 4; The reaction route is as follows:

3. The method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid according to claim 1, characterized in that: The following steps are involved: (1) coupling reaction of the compound of formula 1 with 1,3-dibromo-5-iodobenzene to generate intermediate 5; (2) causing intermediate 5 to undergo a substitution reaction with diethyl phosphite to generate intermediate 6; (3) hydrolyzing the intermediate 6 with bromotrimethylsilane to generate the target product 7; The reaction route is as follows:

4. The method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid according to claim 2, characterized in that: The specific process of step 1 is: mixing compound 1, 1.4-dibromobutane, tetrabutylammonium bromide and potassium hydroxide aqueous solution, reacting at 60-80° C. for 5-8 hours to obtain intermediate compound 2; wherein the molar ratio of compound 1, 1.4-dibromobutane, tetrabutylammonium bromide and potassium hydroxide is 1:8-10:0.01-0.03:10-12.

5. The method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid according to claim 2, characterized in that: The reaction in step 2 is carried out under nitrogen protection, with sodium hydride as a strong base and tetrahydrofuran as a solvent, and the intermediate compound 2 is reacted with diethyl phosphite at a temperature of 0-70°C to obtain the intermediate compound 3; wherein the molar ratio of the intermediate compound 2, sodium hydride and tetraethyl methylene diphosphate is 1:1.5-2.0:1-2.

6. The method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid according to claim 2, characterized in that: The reaction in step three is carried out under nitrogen protection, using 1.4-dioxane as solvent and trimethylsilyl bromide as hydrolysis reagent, so that the intermediate compound 3 undergoes hydrolysis reaction at a temperature of 0-50°C to obtain the final product 4, and methanol is used as a quenching reagent after the reaction; wherein the molar ratio of the intermediate compound 3 to trimethylsilyl bromide is 1:5-10.

7. The method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid according to claim 3, characterized in that: The specific process of step 1 is: dissolving compound 1, 1.3-dibromo-5-iodobenzene, cuprous iodide, 18-crown-6 and potassium carbonate in N,N-dimethylpropylene urea, and reflux reaction under a nitrogen atmosphere to obtain an intermediate compound 5; wherein the molar ratio of compound 1, 1.3-dibromo-5-iodobenzene, cuprous iodide, 18-crown-6 and potassium carbonate is 1:1-3:0.1-0.2:0.05-0.1:2-6.

8. The method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid according to claim 3, characterized in that: The specific process of step 2 is: dissolving intermediate 5, diethyl phosphite, palladium acetate, potassium acetate and dppf in 1.4-dioxane, heating and refluxing to obtain intermediate compound 6, wherein the molar ratio of compound 5, diethyl phosphite, palladium acetate, potassium acetate and dppf is 1:30-40:0.05-0.15:4-8:0.1-0.

5.

9. The method for preparing a self-assembled monomolecular hole transport material based on bisphosphoric acid according to claim 3, characterized in that: The step three is carried out under nitrogen protection, using 1.4-dioxane as solvent and trimethylsilyl bromide as hydrolysis reagent, so that the intermediate compound 6 undergoes hydrolysis reaction at a temperature of 0-50°C to obtain the final product 7, and methanol is used as a quenching reagent after the reaction; wherein the molar ratio of the intermediate compound 6 to trimethylsilyl bromide is 1:10-30.

10. Application of the self-assembled single-molecule hole transport material based on bisphosphoric acid as claimed in claim 1 in an inverted structure perovskite solar cell.

Citation Information

Patent Citations

  • Self-assembled monomolecular layer hole transport material based on alkyl polyphosphoric acid anchoring group and synthesis method and application of self-assembled monomolecular layer hole transport material

    CN116874529A

  • Self-assembled monomolecular layer material based on conjugated linking group, preparation method thereof and solar cell

    CN117659083A

  • Ultraviolet-resistant self-assembly micromolecular hole transport material and preparation method and application thereof

    CN118221726A

Cited By

  • Pyrene-carbazole-based diphosphonic acid self-assembled monomolecular material as well as preparation method and application thereof

    CN120590438A

  • N, N-bis (2-phosphonoethyl) arylamine and preparation method thereof

    CN121319049A

  • 3-hydroxy-4-(4-pyridylazo) anilino-N, N-bis (ethyl-2-phosphonic acid) and preparation method thereof

    CN121362214A

  • 2-(3-hydroxy-4-(N, N-bis (2-phosphonoethyl) amino) phenyl) benzotriazole and preparation method thereof

    CN121426840A

  • Triphenylamine-imino di (ethyl phosphonic acid) and preparation method thereof

    CN121873117A